2016
DOI: 10.1111/jgs.14687
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Hearing Impairment and Incident Frailty in English Community‐Dwelling Older Adults: A 4‐Year Follow‐Up Study

Abstract: ObjectivesTo examine the association between hearing impairment and incident frailty in older adults.DesignCross‐sectional and longitudinal analyses with 4‐year follow‐up using data from the English Longitudinal Study of Ageing.SettingCommunity.ParticipantsCommunity‐dwelling individuals aged 60 and older with data on hearing and frailty status (N = 2,836).MeasurementsHearing impairment was defined as poor self‐reported hearing. Having none of the five Fried frailty phenotype components (slow walking, weak grip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 47 publications
(113 reference statements)
6
69
1
18
Order By: Relevance
“…Table 13 shows the Fried frailty phenotype 10 of participants at baseline. Although all participants met the criteria for 'mild frailty' at baseline, using the Fried phenotype 21 and applying cut-off points for the bottom quintile of grip strength and gait speed from the English Longitudinal Study of Ageing (own data), 225,255 we found that just over of half the sample were frail and only 43% were 'pre-frail'. This was largely explained by poor grip strength, low physical activity and low energy levels in the sample.…”
Section: Feasibility Randomised Controlled Trial: Resultsmentioning
confidence: 99%
“…Table 13 shows the Fried frailty phenotype 10 of participants at baseline. Although all participants met the criteria for 'mild frailty' at baseline, using the Fried phenotype 21 and applying cut-off points for the bottom quintile of grip strength and gait speed from the English Longitudinal Study of Ageing (own data), 225,255 we found that just over of half the sample were frail and only 43% were 'pre-frail'. This was largely explained by poor grip strength, low physical activity and low energy levels in the sample.…”
Section: Feasibility Randomised Controlled Trial: Resultsmentioning
confidence: 99%
“…Our findings are, however, consistent with previous research on the subfactors that were included in our analysis. Several longitudinal studies have shown strong predictive validity of cognitive (namely memory and executive function),47 48 locomotor (gait or chair rise),49–51 sensory (vision and hearing),23 52–54 vitality (hand grip strength or FEV),55–58 and psychological59 indicators in relation to incident loss of ADL and IADL. Studies have also demonstrated associations between indicators of intrinsic capacity and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory: Hearing and vision impairments were measured using self-reported,22 23 validated questions previously demonstrated to be accurate when compared with objective measures. Hearing status was assessed by asking participants to rate their hearing (using a hearing aid if they used one) as excellent, very good, good, fair, or poor.…”
Section: Methodsmentioning
confidence: 99%
“…However, use of this questionnaire to assess the association of frailty with QoL is still scarce, limiting direct comparisons with studies in other settings. Older age, poor financial situation, poor social support, multimorbidity, chronic pain, cognitive impairment, and hearing and vision impairment are associated with both frailty and lower QoL scores [47][48][49][50][51][52][53][54][55][56][57][58]. We therefore adjusted our final regression model for all these variables to estimate the independent association of frailty with QoL.…”
Section: Strengths and Limitationsmentioning
confidence: 99%